What to conserve? Different contexts/different pretexts: three study cases in Argentina - Doumecq, María Belén; Lambaré, Daniela Alejandra; Stampella, Pablo Cesar (Ethnobotany Research and Applications, 2021)
Background: The starting point of this work is Alcorn’s definition of ethnobotany. For this reason, the author goes on to say that the ethnobotanical study object is a sort of text –sensu Ricoeur (1971 cited Alcorn 1995)- whose meaning is partially derived from the natural, social and cultural context. Following this perspective of conservation, the goal of this contribution is to analyse the significance of three tree taxa populations in three areas of Argentina. Methods: Ethnobotanical and historical ethnobotany methodology have been used. Results: The Quebrada peach (Prunus persica), early introduced to Jujuy province, assimilated into local crops and considered as part of local identity. Various citrus (Citrus spp.), also introduced early on by the Jesuits, and highly valued by the locals in Misiones, but rejected in the management of protected areas due to their wild-type and exotic nature-. The tala (Celtis tala), native to the Río de la Plata coastal area, where it lends its name to a particular forest formation, which is often overexploited, and is the focus for the establishment of protected areas. Conclusions: The perusal of these texts (tala, peaches and citrus) demonstrates that they are considered as a part of local identity or heritage no matter a long or short story and native or exotic origin. We also to contribute to the design of conservation strategies from a biocultural perspective. Keywords: Identitary species, Immaterial heritage, Introduction of plants, Landscape construction, Local practices, Perceptions, Qualitative ethnobotany.